Development Of Moderate Composition Of Complex Phytopards Based On Medicinal Plant Raw Materials (Texas Journal of Medical Science, 2024)
This article presents the results of research on the development of hemostat liquid extract and chlorhexidine bigluconate preservative, complex, anti-inflammatory and hemostatic properties of herbal extracts based on local plant raw materials. In particular, the necessary polymer auxiliary substance for the formation of phytoscreens was selected based on experiments, and its moderate concentration of plasticizer glycerin in the polymer mass was justified. Experiments were performed using one of the mathematical planning methods (Latin 3x3 square).